The Issue Of Business Competition Among Padang Restaurants According To Law Number 5 Of 1999 - Sherinda, Ghea Premarsha; Erniwati, Erniwati; Sakinah, Sakinah (Fakultas Hukum Dehasen, 2025)
One of the food businesses that has high competitiveness is Padang restaurants. Padang restaurants are known as delicious restaurants that can adapt to the tastes of the entire community. In the 1950s to 1970s, Padang restaurants experienced rapid growth. Many Minangkabau entrepreneurs opened their businesses in various cities, thus creating business competition. Tight business competition encourages Padang restaurants to continue to improve quality and innovation. However, this competition also poses challenges such as monopolistic practices and unhealthy business competition. The problems in this thesis are the existence of unhealthy competition in the Padang restaurant business and legal settlement efforts that can be taken if a dispute occurs between Padang restaurants. This problem was triggered by a 38-second viral video showing the actions of a number of people removing the